2017
DOI: 10.1073/pnas.1711058114
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor beta and NCOA4 regulate terminal erythrocyte differentiation

Abstract: An effect of thyroid hormone (TH) on erythropoiesis has been known for more than a century but the molecular mechanism(s) by which TH affects red cell formation is still elusive. Here we demonstrate an essential role of TH during terminal human erythroid cell differentiation; specific depletion of TH from the culture medium completely blocked terminal erythroid differentiation and enucleation. Treatment with TRβ agonists stimulated premature erythroblast differentiation in vivo and alleviated anemic symptoms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 49 publications
(71 reference statements)
5
39
0
Order By: Relevance
“…First, NCOA4 is expressed at high levels in maturing orthocromatic erythroblasts (7); second, in vitro (4,8) and ex vivo data (9) suggest that NCOA4 is required for erythroid cells differentiation and hemoglobinization, modulating iron incorporation into heme. An erythropoietic role for NCOA4 was suggested also in vivo in zebrafish embryos treated with morpholinos to Ncoa4 (4).…”
Section: Introductionmentioning
confidence: 99%
“…First, NCOA4 is expressed at high levels in maturing orthocromatic erythroblasts (7); second, in vitro (4,8) and ex vivo data (9) suggest that NCOA4 is required for erythroid cells differentiation and hemoglobinization, modulating iron incorporation into heme. An erythropoietic role for NCOA4 was suggested also in vivo in zebrafish embryos treated with morpholinos to Ncoa4 (4).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that mice unable to efficiently degrade ferritin may eventually develop an 'overflow' of iron into the cytoplasm leading to higher susceptibility to oxidative damage as discussed in greater detail below. NCOA4 appears to be more important at various stages of development as NCOA4 KO mice examined at the immediate postnatal period showed a more severe anemia [34]. This study suggests a differential temporal requirement of NCOA4-mediated ferritinophagy in periods of high iron demand.…”
Section: Ncoa4 Mediates Ferritin Iron Release To Support Erythropoiesismentioning
confidence: 63%
“…Subsequent studies suggested that NCOA4 also regulated a number of additional nuclear receptors [29][30][31][32][33]. A recent study suggested that NCOA4 can be regulated by thyroid hormone, promoting NCOA4 recruitment to chromatin regions that induce a transcriptional program supporting erythropoiesis [34]. Finally, Bellelli et al suggest NCOA4 inhibits DNA replication origin activation by binding to the MCM2-7…”
Section: Ncoa4 Mediates Ferritin Transport To the Lysosome For Degradmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, with respect to the role of Ncoa4 in modulating the response to acute erythropoietic stressors, we refer Nai and colleagues to multiple prior published studies showing that genetic ablation of Ncoa4 affects erythropoiesis acutely, including our own work in an orthogonal zebrafish model. 8,9 Furthermore, we note our findings in our erythroid specific Ncoa4 knockout model (Ncoa4 fl/fl ; EpoR-Cre) where these animals have an increased sensitivity to acute erythropoietic stress upon phenylhydrazine-induced anemia and have an extrareliance on compensatory mechanisms to support full recovery of an anemia. These findings all support our conclusions regarding the role of Ncoa4 in supporting erythropoiesis.…”
mentioning
confidence: 65%